Assessment of Selected Proximate and Heavy Metals in Enset Products Collected from Tepi Market, Southwestern Ethiopia - Shisho Haile Geleta (Journal of Food Quality)
This study focused on determining selected proximate compositions, such as moisture content, ash content, crude fibre content, and crude fat content, of kocho and bulla enset products collected from Bechi, Fide, Yeki, Zinki, Addis Alem, and Korcha kebeles of Yeki woreda. Besides, heavy metals such as iron, copper, manganese, zinc, and lead have been analyzed. The result showed that all proximate compositions analyzed agree with other conducted researches, except moisture content because of heavy rainfall in Yeki woreda. On the other hand, the results obtained for iron and zinc were higher than the permissible limit set by international standards, while that of manganese was slightly higher than the standard limit. On the other hand, the results obtained for copper were below the permissible limit set, while lead was not detected in all samples. Therefore, the investigated kocho and bulla products can provide an appreciable amount of analyzed minerals.